2022
DOI: 10.1088/1361-6641/ac6128
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the analog/RF and linearity performances of FinFET using high threshold voltage techniques

Abstract: One of the severe issues of the downscaling of semiconductor devices is the threshold voltage reduction which significantly increases the leakage current. Thus, high threshold voltage (HVT) techniques are required to bring down the leakage hike for improved performances. In this paper, for the first time, we investigate the analog/RF and linearity performances of silicon (Si) FinFET by employing HVT techniques. Using well-calibrated TCAD models, to mitigate the leakage current, we analyzed the following approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Using high Vth techniques (HVT) like enhanced channel doping, drain-side underlap and increased gate lengths in Si-FinFETs results in superior analog FoMs like transconductance, cut-off frequency, output resistance, gain-bandwidth product. SOI-FinFETs with HVT show merit in intrinsic gain and linearity parameters [30]. Several variations of the FinFET architecture, like use of high-K gate oxides, SOI structure, ferroelectric FinFETs and their circuit performance have been presented in detail in [31].…”
Section: Finfetsmentioning
confidence: 99%
“…Using high Vth techniques (HVT) like enhanced channel doping, drain-side underlap and increased gate lengths in Si-FinFETs results in superior analog FoMs like transconductance, cut-off frequency, output resistance, gain-bandwidth product. SOI-FinFETs with HVT show merit in intrinsic gain and linearity parameters [30]. Several variations of the FinFET architecture, like use of high-K gate oxides, SOI structure, ferroelectric FinFETs and their circuit performance have been presented in detail in [31].…”
Section: Finfetsmentioning
confidence: 99%
“…Venkkataraman et al [14] derived the expression of threshold voltage considering the Si strain effect on the SiGe channel. Fei Ding et al [15] proposed a p-channel FinFET with a heterogeneous channel region (Si-Si 0.9 Ge 0.1 ) and compared it with a conventional p-channel FinFET. It was observed that the hetero-channel structure provides more ON current than the conventional one, and a low Ge mole fraction can enhance performance.…”
Section: Introductionmentioning
confidence: 99%
“…From an application point of view, the extraction of linearity parameters of semiconductor devices must be taken into consideration as this has been one of the crucial parameters in order to reduce the intermodulation and receive high order harmonics as the output. On the other hand, sensitivity depends on device linearity, distortion and transconductance parameters [17,18]. The various non linearity parameters such as VIP2, VIP3, IMD3, g m2 & g m3 [19,20] for different ferroelectric thicknesses have been analyzed.…”
Section: Introductionmentioning
confidence: 99%